Wireless Electric Road Systems - Technology Readiness and Recent Developments - Wendt, Andreas; Arnold, Maximilian; Ezer, Oren; Hoppe, Axel; Kanesaki, Masaki; Kneidl, Maximilian; Kurpat, Thorsten; Kuhl, Alexander; Maemura, Masato; Masuch, Michael; Pollauer, Alexander; Schmidt, Robert; et al. (Proceedings of 2024 IEEE Wireless Power Technology Conference and Expo, WPTCE 2024, 2024)
The progress in dynamic wireless power transfer (D-WPT) led to the availability of wireless Electric Road Systems (wERS) that offer smart infrastructure solutions that can substantially reduce transport emissions and electric vehicle (EV) range anxiety. The basis of this technology is resonant Wireless Power Transfer (WPT), which was first demonstrated in the 1890s by Nikola Tesla and has since been developed for various applications. This paper illustrates the state of Electreon's wERS technology by insights from current pilot projects as well as progress from active R&D activities.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ELINA; EMADI; ERS; E|MPOWER; Global Warming; WPT